EXPERIMENTAL VERIFICATION AND REVIEW PERFORMANCE OF THE MODIFIED TRIANGULAR PLAN FORM WEIR - JALIL, SHAKER A.; JAFAR, RONDIK A.; IBRAHIM, SAFA S. (Journal of Duhok University, 2021)
Weirs are discharge measurement structures have different geometrical shapes. The performances of the modified triangular plan form weirs were studied under free-flow condition. Three groups of weirs were tested experimentally. The first group has a flat top; the second has one slope and the third has two slopes. Each group has three vertex angles (60o, 90oand 120o) with constant height. The hydraulicperformances of weirs are based on the ability to pass the discharge for certain head flow and on the value of the coefficient of discharge. The values of discharge and the coefficient were compared with earlier studies being carried on conventional normal weir, broad crest, triangular plan-form and different labyrinth weirs. All the groups show better performance than conventional shaped and broad weir. The magnification of the actual discharge to the discharge of broad crested weir is more than one and the best one is the first in the third group, while the vertex angle is (60o) for the second and third group and (120o)for the first. The performance of the third group is better than rectangular labyrinth weirs, and it is compatible with the triangular labyrinth. The discharge coefficient decreases with the increase of relative value of the head to the height of weir except for the first group. Equations for predicting coefficient of discharge are proposed within the limitations of this test.